2019
DOI: 10.1093/ckj/sfz105
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary biomarkers and disease progression in adults with autosomal dominant polycystic kidney disease

Abstract: Background Height-adjusted total kidney volume (htTKV) is considered as the best predictor of kidney function in patients with autosomal dominant polycystic kidney disease (ADPKD), but its limited predictive capacity stresses the need to find new biomarkers of ADPKD progression. The aim of this study was to investigate urinary biomarkers of ADPKD progression. Methods This observational study included ADPKD patients, and two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The disease progression predictive power of high levels of uMCP1 was also indicated by a study on mice with PKD where uMCP1 increased earlier than serum creatinine and blood urea nitrogen [26]. It has been reported that a hypoxic environment induced by the pressure of growing cysts stimulates the expression and release of hypoxiainducible factor-1α and the pro-angiogenic gene vascular endothelial growth factor, which in turn, can upregulate the expression of MCP1 [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease progression predictive power of high levels of uMCP1 was also indicated by a study on mice with PKD where uMCP1 increased earlier than serum creatinine and blood urea nitrogen [26]. It has been reported that a hypoxic environment induced by the pressure of growing cysts stimulates the expression and release of hypoxiainducible factor-1α and the pro-angiogenic gene vascular endothelial growth factor, which in turn, can upregulate the expression of MCP1 [27].…”
Section: Discussionmentioning
confidence: 99%
“…In an ADPKD cohort, uMCP1 correlated positively with height-adjusted TKV and negatively with the eGFR slope. Furthermore, a multivariate model including urinary levels of β2-microglobulin, MCP1 and vascular endothelial growth factor improved the ability to predict the decline of eGFR in ADPKD patients compared with height-adjusted TKV alone [27]. Likewise, baseline uMCP1, as well as the β-2-microglobulin, were associated with eGFR decline in the ADPKD cohort, and, when it was added to a model containing conventional risk markers that explained annual changes in eGFR its performance significantly increased [13].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ADPKD, the inflammatory markers MCP-1 and macrophage migration inhibitory factor (MIF) are elevated in the urine and cyst fluid (Zheng et al, 2003;Meijer et al, 2010;Kim and Tam, 2011;Chen et al, 2015). Urinary MCP-1 correlates with TKV and predicts progression to CKD stage 3 (Meijer et al, 2010;Chapman et al, 2012;Messchendorp et al, 2018;Segarra-Medrano et al, 2020). In an inducible knock-out model of Pkd1, MCP-1 upregulation, independently of tubular injury, caused monocyte infiltration.…”
Section: Amp-activated Protein Kinase Interacts With Other Processes ...mentioning
confidence: 98%
“…Signaling through EGF receptors is essential for the growth, migration, differentiation, and proliferation of cells. In ADPKD, the concentration of EGF in the cystic fluid is significantly decreased, and EGF plasma concentrations and urinary excretion are lower in patients with ADPKD than in controls [ 34 , 35 ]. In addition, urinary EGF levels were significantly correlated with eGFR levels in ADPKD patients, showing that tubular dysfunction may also be associated with renal failure [ 34 ].…”
Section: New Biomarkers In Adpkdmentioning
confidence: 99%
“…In addition, tubular hypoxia inducible factor 1α (HIF-1α) was described as having a strong cyst-growth-promoting effect in ADPKD mice [ 42 ]. Urinary levels of the biomarkers associated with renal ischemia, such as HIF-1α, pro-angiogenic gene VEGF, and chemotactic factor for monocyte MCP-1, were elevated in patients with ADPKD; they are correlated with htTKV and may, therefore, be used as biomarkers of kidney injury in ADPKD patients with a mild reduction in GFR [ 35 ].…”
Section: New Biomarkers In Adpkdmentioning
confidence: 99%